Media Interaktif Pembelajaran Berbasis Multimedia menggunakan Adobe Flash untuk TK dan PAUD - Aryanti, Putri Gea; Lailany, Afyra Ar’bah; Amelia, Ika; Regita, Anggit Nur Hannaa; Setiawan, Kiki; Yel, Mesra Betty (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
Preschool (TK) or Early Childhood Education (PAUD) plays an essential role in shaping the foundation of knowledge, attitudes, and skills in children. The primary focus of early childhood education goes beyond stimulating, guiding, nurturing, and providing learning activities at school. Media learning, incredibly educational interactive media, becomes crucial in motivating and educating children. This study focuses on developing interactive multimedia-based learning media using Adobe Flash for TK and PAUD at TK Bamadita Rahman. Through interviews with the school principal and teachers, a needs analysis was conducted to evaluate the implementation of interactive learning media. The research addresses conventional learning challenges by designing an engaging, child-friendly interactive media application. The objectives include creating interactive media, serving as a reference for play-based learning activities, implementing interactive media, and assessing its effectiveness in TK and PAUD Bamadita Rahman. The study concludes that the learning application using Adobe Flash has been successfully designed, has the potential to cultivate an interest in animation among the younger generation, and enhances the efficiency of the teaching and learning process.